REGARD CRITIQUE SUR LES CONCEPTIONS TRADITIONNELLE ET BIBLIQUE DU MARIAGE. CAS DES TOPOKÉ DE LUETÉ EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO - Baelongandi, Augustin SOMBO; Botolome, Lambert FUNGA; Gaby, EKAKWA Ewolo (IJRDO - Journal of Social Science and Humanities Research, 2022)
Originally the marriage symbolizes the union of two families for the eternity. The divorce not existing in the majority of the African cultures. This reality exists on this day at the Topoke people in RDC. According to the custom, after the husband’s death, the widow could marry one of the brothers of his defunct husband. This logic that exists again in some tribes until our days, testify of the eternity of the tie of the marriage in Africa.